Interprofessional Education in Medical-Legal Partnerships (MLPs) to Address Social Determinants of Health - Gard, Lauren A; Bartell, Tami; Shah, Anuj K; Setrini, Alice B; Sheehan, Karen; Miller, Corinne H; Paquette, Erin T (Journal of health care for the poor and underserved, 2021)
Medical-legal partnerships (MLP) address legal needs that contribute to health inequities. Health providers express discomfort accessing legal services and a desire for greater training, however best practices remain unclear. We conducted a scoping literature review and interviews with key informants to identify essential components of MLP training and best practices in MLP training. Twenty-one articles out of an initial 1,247 met criteria. Most learners were medical (11; 52%) or law (13; 62%) students or residents (12; 57%). Training was primarily led by lawyers (18; 86%). Educational approaches included didactics (15; 71%). Content was focused on skill-acquisition (18; 86%). Most training was presented as stand-alone (5; 24%) courses. Essential skills included issuespotting, adaptability, and trauma-informed care. Medical-legal partnerships make use of varied perspectives to address unmet legal needs. This review helped identify best practices in training and a need for future study on evaluation. Future research should explore how best to evaluate the effectiveness of MLP training.